2001
DOI: 10.1038/sj.leu.2402004
|View full text |Cite
|
Sign up to set email alerts
|

Purified autologous grafting in childhood acute lymphoblastic leukemia in second remission: evidence for long-term clinical and molecular remissions

Abstract: Autologous transplantation is a treatment option for relapsed childhood acute lymphoblastic leukemia (ALL) in second complete remission (CR2) when a suitable donor is not available. In an attempt to prevent relapses originating from graft leukemic contamination, the experimental protocol of in vitro purification of leukapheretic products with monoclonal antibodies (MoAbs), previously reported for adults, was adopted in 11 of 12 consecutive patients (median age, 9 years) with B cell precursor ALL in CR2 after l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Informed consent was obtained from the parents or guardians for all patients. 26 All consecutive low-risk relapse patients are reported.…”
Section: Enrollment and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Informed consent was obtained from the parents or guardians for all patients. 26 All consecutive low-risk relapse patients are reported.…”
Section: Enrollment and Characteristicsmentioning
confidence: 99%
“…26 Briefly, the first step of immunorosetting aimed to reduce the total cell count, by eliminating CD11b þ cells. The second step, using a column inserted in a SuperMACS (Miltenyi Biotec GmbH, Bergisch Gladbach, Germany) magnetic cell separator device, was performed after incubation with anti-CD19 MoAbs conjugated with paramagnetic microbeads (Miltenyi Biotec) to deplete virtually all CD19 þ cells and recover most CD34 þ cells.…”
Section: Manipulation Of the Graftmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 The collection of large doses of HSC allows purification procedures, aiming at achieving complete removal of possibly contaminating leukemic cells. 8,9 Even though autologous transplantation is widely used in adults, limited experiences of PB mobilization have been reported so far in children, other than in solid tumors. 10,11 In this study we report on the effectiveness of the new regimen 'DIAVE' in children with AL in terms of the high proportion of patients 'mobilizing' and high level of 'mobilized stem cells'.…”
mentioning
confidence: 99%
“…15,16 Indications for auto-HSCT are limited to a small subset of children with either late marrow relapse or extramedullary recurrence. 17,18 A recent survey by the European Bone Marrow Transplant group showed that prior to May 1996, the majority of allografts (70%) were performed from HLA MSDs. During the last 10 years, the number of alternative HSCTs, including UDs, partially matched family donor and UCB HSCTs, has increased significantly (P ¼ o0.0001) and reached 61% of the allografts carried out between 1999 and 2002 ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%